ANALISIS PERBEDAAN TEKANAN DARAH PADA PASIEN STROKE ISKEMIK DAN STROKE HEMORAGIK DI RSU BINA KASIH MEDAN: ANALYSIS OF DIFFERENCES IN BLOOD PRESSURE ON THE PATIENTS OF ISCHEMIC AND HEMORRHAGIC STROKE AT BINA KASIH GENERAL HOSPITAL, MEDAN - Safithri, Ridha; Siregar, Julahir Hodmatua; Makmur, Tri; Veronica, Sinta (Fakultas Kedokteran Universitas Islam Sumatera Utara, 2025)
Background: Stroke is an acute neurological disorder that can be caused by ischemia or hemorrhage and lasts more than 24 hours or can cause death. Stroke has many risk factors, one of which is hypertension. hypertension is defined when systolic blood pressure is more than 140 mmHg or diastolic blood pressure is more than 90 mmHg. Objective: To determine the difference in blood pressure in ischemic and hemorrhagic stroke. Methods: Analytical observational study cross sectional approach with purposive sampling technique. The sample size was 66 medical record data calculated using the sample size formula for analysis using Kolmogorov-Smirnov Z analysis. Data collection techniques using secondary data. Resultls : The results of the Kolmogorov-Smirnov Z test showed that there was a difference in blood pressure between ischemic stroke and hemorrhagic stroke (p = 0.039). Conclution: There is a difference between blood pressure in ischemic stroke and hemorrhagic stroke. AbstrakLatar belakang: Stroke merupakan gangguan neurologis akut yang dapat disebabkan oleh iskemia atau perdarahan dan berlangsung lebih dari 24 jam atau dapat menyebabkan kematian. Stroke memiliki banyak faktor risiko, salah satunya adalah hipertensi. Hipertensi diartikan ketika tekanan darah sistolik lebih dari 140 mmHg atau tekanan darah diastolik lebih dari 90 mmHg. Tujuan: Untuk mengetahui perbedaan tekanan darah pada stroke iskemik dan hemoragik. Metode: Studi observasional analitik pendekatan cross sectional dengan Teknik pengambilan sampel purposive sampling. Besar sampel sebanyak 66 data rekam medik yang dihitung dengan menggunakan rumus besar sampel untuk analisis mengunakan analisis Kolmogorov-Smirnov Z. Teknik pengambilan data menggunakan data sekunder. Hasil: Dari hasil uji Kolmogorov-Smirnov Z menunjukkan ada perbedaan tekanan darah antara stroke iskemik dan stroke hemoragik (p = 0,039). Kesimpulan: Terdapat perbedaan antara tekanan darah pada stroke iskemik dengan stroke hemoragik.